Lactylation and its roles in diseases: a systematic bibliometric exploration of the research landscape - Li, Mengjia; Liu, Yuhang; Jiang, Chuhan; Zhang, Shiyu; Nan, Mengyu; Liu, Jiaxi; Han, Yangyang (Frontiers in Oncology, 2025)
BackgroundLactylation, a post-translational modification (PTM), has gained attention for its role in disease pathogenesis, particularly in cancer and immune regulation. Initially viewed as a glycolysis byproduct, lactate is now recognized as a precursor for histone lysine lactylation (Kla), which regulates gene transcription and epigenetic processes. Dysregulation of lactylation is linked to malignancies, inflammation, and metabolic diseases. Despite growing research, a systematic bibliometric analysis of lactylation remains absent. This study addresses this gap by analyzing lactylation research from 2019 to 2024, focusing on its disease-related mechanisms and therapeutic potential.MethodData were extracted from the Web of Science Core Collection (2019–2024), yielding 198 relevant articles after screening. Bibliometric analysis was conducted using Microsoft Excel, VOSviewer, Scimago Graphica and CiteSpace. Excel tracked publication trends, VOSviewer generated author density maps, and CiteSpace visualized collaboration networks, co-cited references, and keyword clusters. Scimago Graphica generated Map of country cooperation networks. The study identified research trends, collaborative patterns, and emerging hotspots in lactylation research.ResultLactylation research has surged exponentially since 2022, with China as the primary contributor (92.42% of publications). Dominant keywords converge on lactylation’s role as a direct epigenetic regulator of gene activation, enabling transcriptional reprogramming in diseases; Lactylation drives bladder cancer progression via immunosuppressive genes, mediates myoblast differentiation for muscle repair, and disrupts signaling through non-histone targets; Emerging focus on “differentiation” and “metabolic regulation” highlights its potential as a cellular reprogramming target, crucial for advancing regenerative medicine and combating inflammation-linked pathologies.ConclusionThis study provides the first bibliometric analysis of lactylation research, highlighting its rapid growth and global significance. China leads the field, with extensive contributions from its institutions. Lactylation’s role in disease mechanisms, particularly cancer and immune regulation, underscores its therapeutic potential. Emerging research on differentiation and metabolic regulation offers new directions for future studies. Further investigation into lactylation’s molecular mechanisms and therapeutic applications is essential for advancing disease diagnosis and treatment.